Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Traversés féministes transnationales: du néolibéralisme et de la critique radicale - Mohanty, Chandra Talpade (Les cahiers du CEDREF, 2015)
Qu’est-il arrivé à la recherche et à la théorie féministe dans notre culture universitaire néolibérale ? Les transformations globales et nationales dans l’activisme du mouvement social et les projets de recherche féministe ont-ils dépolitisé les projets intellectuels féministes, antiracistes, femmes-de-couleur1 et transnationaux ? J’examine ici les diverses façons dont mon propre travail a voyagé et ce qu’il a perdu (et trouvé) en étant traduit dans différents contextes, pour offrir quelques réflexions sur les effets des paysages géopolitiques néolibéraux obsédés par la sécurité nationale et sur les cadres intellectuels postmodernes, ainsi que sur la théorisation féministe intersectionnelle et le travail de solidarité transnationale. La façon dont mon travail a été adapté et développé dans certaines communautés de chercheuses et d’activistes féministes marginalisées me semble offrir notamment d’intéressantes leçons pour nous toutes, les féministes universitaires, en indiquant les limites des projets de savoirs féministes postmodernes dans l’Université néolibérale.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiracisme; approches et analyses; capitalisme; cours; discipline; dépolitisation; féminisme décolonial; féminisme postmoderne; histoire et politique; intersectionnalité; militance; néolibéralisme; pol4212; postmodernisme; premier cycle; périodes historiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; université néolibérale

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art